Efficacy of cadonilimab in combination with nimotuzumab and AG regimen in TMB-H/KRAS wild-type advanced pancreatic cancer: a case report - Tang, Zhiwei; Hu, Jiegang; He, ZhongShi; Zhang, Dongdong (Frontiers in Immunology, 2025)
BackgroundAdvanced pancreatic cancer carries a dismal prognosis. Current chemotherapy provides limited survival benefit while causing substantial toxicity. Despite numerous trials, combining gemcitabine with other cytotoxic or targeted agents has not significantly improved outcomes, highlighting the urgent need for novel therapeutic strategies.Case presentationThis report describes a 56-year-old male diagnosed with stage IVB pancreatic tail adenocarcinoma, characterized by a high tumor mutational burden (TMB-H) and a KRAS wild-type status. The patient showed a significant therapeutic response and an improved quality of life after receiving a novel four-drug combination regimen. The treatment included cadonilimab (a PD-1/CTLA-4 bispecific antibody), nimotuzumab (an EGFR monoclonal antibody), albumin-bound paclitaxel, and gemcitabine. After two cycles, the primary pancreatic lesion reduced by 37%, and there was substantial shrinkage of hepatic metastases. Continued treatment maintained partial remission (PR), with progression-free survival (PFS) lasting over seven months and manageable toxicity.ConclusionThis case highlights the potential of the combination of cadonilimab, nimotuzumab, albumin-bound paclitaxel, and gemcitabine as an effective, low-toxicity treatment option for patients with TMB-H/KRAS wild-type advanced pancreatic cancer.